PENGARUH NET PROFIT MARGIN, CURRENT RATIO DAN DEVIDEN PAYOUT RATIO TERHADAP PRICE EARNING DAN PRICE BOOK VALUE - Siti Aisyah (Jurnal Manajemen FE-UB, 2015)
Invesment in stocks is a high-risk invesment, where investors can gain a lot and vice versa loss is not small. Therefore, investors are required to be through in decision-making. This study aimed to analyze the influence of the Net Profit Margin and Deviden Payout Ratio Current Ratio, the Price Earning Ratio and Price Book Value. Furthermore, the independent variaable which is the most dominant influence on consumer goods companies listed in Indonesia Stock Exchange 2011-2013.  Sample used in this research are 16 firms that registered in Stock Exchange Indonesia and Indonesia Capital Market Directory (ICMD) during the period 2011-2013. Metode sampling is done by using purposive sampling. The method used in this study using multiple linear regression analysis. The result of the independent variable on earning price ratio. Found that the current ratio and the net profit margin is not exhibited significantly negative effect means that the hypothesis is rejected, while the dividend payout ratio significantly influence the price earnings ratio means the hypothesis is accepted. The test results of independent variables on price book value. It was found that the net profit margin and divident payout ratio positive significant effect on price book value hypothesis is accepted. While the current ratio does not significantly hypothesis is rejected. And the results of these variables together from the first model and the second model found that the net profit margin, current ratio, and dividend payout ratio positive significant effect on the price earnings ratio and price book value. While most dominant variable effect on the net profit margin price book value.  Keywords : Net Profit Margin Current Ratio, Dividend Payout Ratio, Price Earning Ratio and Price Book Value